Photographs - Selby, Clive Herbert, 1908-1996. (1934)
Three photographs taken at Wau and one at Salamaua.
Manuscript reference: NLA MS 3763.
Keywords: Wau (Papua New Guinea) -- Pictorial works; Salamaua (Papua New Guinea) -- Pictorial works